Measuring small and medium enterprises' (SMEs) inclination to technological innovation - Roa, Arlynne Sison (University of the Philippines Diliman, 2004)
The success of the Philippine economy depends on Small and Medium Enterprises (SMEs) that constitute 99.6 percent of total firms in the country and employ 69.9 percent of the labor force. Sixty percent of SMEs are exporters. Sadly, although SMEs outnumber large companies, it is the latter that generate 69 percent of the country's revenues. Various government programs have not helped improve SME productivity, which is still low compared to other Asian countries. Despite the number of local and international studies on SMEs and innovation, the programs government has developed to support their sustainability has not recognized innovation as a critical success factor. Moreover, there is no existing tool that measures SMEs' inclination to innovation, much less for technological innovation, in the Philippines. This project designed a tool that measured SMEs' inclination to technological innovation. Data gathered from this tool will reflect SMEs' current outlook towards innovation. The research instrument was developed using the guide for data collection on technological innovation, also known as the "Oslo Manual" developed by the Organization for Economic Cooperation and Development (OECD). OECD has compiled research on innovation that has identified factors that are mostly based around learning and organization. The primary research method was a survey and was complemented by interviews. Survey results indicate Philippine SMEs are generally inclined to innovation particularly in idea generation and learning. Owners and managers of firms view the importance of innovation from a marketing perspective while employees generally see innovation as a way of improving productivity. The survey was validated using two external criterion variables : new products and services and income generated from these new products and services. The test posted a high reliability index of 0.95. The positive correlation coefficients and t-values of the two external variables also show a fair level of significance and indicate the external validity of the survey. Some barriers in the gathering of statistical data were identified and recommendations for further study on innovation in SMEs include research on enterprise innovations.